2015
DOI: 10.1089/ten.tea.2014.0455
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid-Based Polymers for Guided Bone Regeneration Using Bone Morphogenetic Protein-2

Abstract: Bone morphogenetic protein-2 (BMP-2) is used clinically to promote spinal fusion, treat complex tibia fractures, and to promote bone formation in craniomaxillofacial surgery. Excessive bone formation at sites where BMP-2 has been applied is an established complication and one that could be corrected by guided tissue regeneration methods. In this study, anti-inflammatory polymers containing salicylic acid [salicylic acid-based poly(anhydrideester), SAPAE] were electrospun with polycaprolactone (PCL) to create t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…SAPAE have been synthesized by chemically incorporating salicylic acid, a nonsteroidal anti-inflammatory drug, that reduces the production of pro-inflammatory cytokines within a polyanhydride [ 145 ]. Subramanian et al [ 146 ] tested SAPAE membrane as a physical barrier and localized salicylic acid delivery system to restrict BMP-2 activity to a specified region. The data indicated that SAPAE polymer membranes have potential application in GBR and GTR procedures and as a barrier to excessive bone formation for diabetes.…”
Section: Resorbable Membranes Based On Other Polymermentioning
confidence: 99%
“…SAPAE have been synthesized by chemically incorporating salicylic acid, a nonsteroidal anti-inflammatory drug, that reduces the production of pro-inflammatory cytokines within a polyanhydride [ 145 ]. Subramanian et al [ 146 ] tested SAPAE membrane as a physical barrier and localized salicylic acid delivery system to restrict BMP-2 activity to a specified region. The data indicated that SAPAE polymer membranes have potential application in GBR and GTR procedures and as a barrier to excessive bone formation for diabetes.…”
Section: Resorbable Membranes Based On Other Polymermentioning
confidence: 99%
“…There are only a few reports on the effects of ASA on stem cell differentiation. With its inhibiting effect on tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) production, aspirin has been shown to promote the osteogenesis of bone MSC in vitro, improve calvarial bone repair in vivo (Cao et al, 2015), and limit ectopic bone formation caused by BMP-2 treatment (Subramanian et al, 2015). (Alcaraz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Subramanian et al produced thin flexible electrically driven membranes consisting of a copolymer of salicylic acid/succinic anhydride (SAPAE) and polycaprolactone (PCL) for use in bone tissue regeneration. These membranes were able to release salicylic acid during hydrolysis of one of the polymeric components [ 14 ]. Some studies described the effects of DIC release on reducing host response to the implanted foreign body.…”
Section: Introductionmentioning
confidence: 99%